Biological sovereignty against the bioethical imperative: morphological freedom and obligatory moral enhancement - Villarreal García, Alicia (2024)
This article examines the normative tension between the right to bodily and mental modification, understood as morphological freedom, and the utilitarian mandate of obligatory moral enhancement, as the latter has been formulated by Persson and Savulescu (2012b). It proceeds from the hypothesis that this mandate presupposes that the biotechnological modification of affective and empathic traits, principally through oxytocinergic pathways, by itself guarantees more just conduct, without such modification violating the moral agency of the intervened subject. Against this hypothesis, it is argued that the imposition of obligatory moral enhancement, insofar as it dispenses with the agent's deliberative consent and conscious veto over his or her own mental states, does not produce genuine moral improvement but rather substitutes ethical judgment with neurochemical automatism, thereby destroying the very condition of possibility of the moral agency it purports to optimize. Three bodies of literature are articulated to sustain this thesis: the liberal defense of morphological freedom and biological self-determination (Harris, 2011; Sandberg, 2013), the neuroscientific evidence on the empirical limits of available pharmacological enhancers (Rakić, 2017), and the metaethical critique of the political instrumentalization of the body (Sandel, 2007; Sparrow, 2014b). It concludes by proposing a model of adjunctive and voluntary enhancement that preserves deliberation as a necessary condition for any genuine moral progress.